La mise à distance dans le travail social : effet sur l’épuisement émotionnel - Francois Melou; Lionel Dagot (Sociétés et Jeunesses en Difficulté)
The professional exhaustion is a widely commented theme, it can concern the set of the individuals in the work. An emotional request is a factor increasing the risk of exhaustion in the workplace. Therefore, the social work is the place of a stress associated with an emotional work. Indeed, this professional come true their varied missions but whatever these bet, they involve to manage the feelings. In his working, everyday life they are to impact on the difficult situations with vulnerable public.The second phase uses a questionnaire based on the Shirom Melamed burnout Measurment (SMBM) which measures the emotional exhaustion, the physical fatigue and the cognitive tiredness. We are questioning the depersonalization and the disengagement effect on emotional exhaustion and emotional dissonance within a sample of social workers (N=116). From two follow-up studies, one by conversations and the other one by questionnaire, we highlight a potential of depersonalization and disengagement in emotional exhaustion and emotional dissonance of social workers.From this work arises a theory which would make the depersonalization and the disengagement two antagonist entities acting on the emotional social exhaustion of this worker’s sample.